Hydrogels assembled from hybrid of whey protein amyloid fibrils and gliadin nanoparticles for curcumin loading: Microstructure, tunable viscoelasticity, and stability - Zhu, Yuqing; Han, Yalan; Peng, Shengfeng; Chen, Xing; Xie, Youfa; Liang, Ruihong; Zou, Liqiang (Frontiers in Nutrition, 2022)
Food grade hydrogel has become an ideal delivery system for bioactive substences and attracted widely attention. Hybrids of whey protein isolate amyloid fibrils (WPF) and gliadin nanoparticles (GNP) were able to assemble into WPF-GNP hydrogel at a low protein concentration of 2 wt %, among which WPF and GNP were fabricated from the hydrolysis of whey protein isolate under 85 °C water bath (pH 2.0) and antisolvent precipitation, respectively. Atomic force microscope (AFM) images indicated that the ordered nanofibrillar network of WPF was formed at pH 2.0 with a thickness of about 10 nm. Cryo-SEM suggested that WPF-GNP hydrogel could arrest GNP within the fibrous reticular structure of the partial deformed WPF while the hybrids of native whey protein isolate (WPI) and GNP (WPI-GNP hybrids) only led to protein aggregates. WPF-GNP hydrogel formed at pH 4.0 (85 °C, 3 h, WPF:GNP=4:1) possessed the largest elastic modulus (G'=419 Pa), which far exceeded the elastic modulus of the WPI-GNP hybrids (G'=16.3 Pa). The presence of NaCl could enhance the strength of WPF-GNP hydrogel and the largest value achieved at 100 mM NaCl ( 105 mPa) in the range of 0 500 mM due to electrostatic screening. Moreover, WPF-GNP hydrogel showed a high encapsulation efficiency for curcumin, 89.76%, 89.26%, 89.02%, 85.87%, 79.24% for pH 2.0, 3.0, 4.0, 5.0, 6.0, respectively, which suggested that the formed hydrogel possess good potential as a delivery system. WPF-GNP hydrogel also exhibited good protect effect on the photodegradation stability of the loaded curcumin with the retention up to 75.18% after hydrogel exposed to ultraviolet radiation for 7 days. These results suggested that the viscoelasticity of WPF-GNP hydrogel was tunable via pH-, ion-, or composition- adjustment and the hydrogel showed excellent protection on the thermal and photodegradation stability of curcumin.